Incidence of Hyperamylasemia Leading to Respiratory Failure in Patients of Organophosphate Poisoning (Medical Forum Monthly, 2024)
Objective: To determine the frequency of Hyperamylasemia leading to respiratory failure in patients of organophosphate poisoning.Study Design: Observational / descriptive study.Place and Duration of Study: This study was conducted at the Department of Medicine Dow University of Health Sciences, Karachi from June 2014 to June 2015.Materials and Methods: A total of 168 patients of Organophosphate poisoning fulfilling the inclusion criteria were included in the study. Blood was drawn after aseptic measures by a trained phlebotomist for Serum Amylase level and Arterial blood gases. Value more than 101U/L was taken as hyperamylasemia. PaO2 less than 60mmHg or PCO2 greater than 55mg was labeled as respiratory failure. All information was noted on proforma.Results: There were 59% were male and 41% were female. Frequency of hyperamylasemia in patients of organophosphate poisoning was 44%. Frequency of respiratory failure in hyperamylasemia in patients was observed in 68%. Respiratory failure was significantly high in male than female (70% vs. 30%; p=0.019). Conclusion: Hyperamylasemia is more frequently seen in organophosphate poisoning. In patients with respiratory failure the mortality is very high; therefore we recommended early diagnosis, careful monitoring and appropriate management of complications in reducing the mortality rate.